Modeling Dynamic Hysteresis Curves in Amorphous Magnetic Ribbons - Krzysztof Chwastek; Mariusz Najgebauer; Paweł Jabłoński; Tomasz Szczegielniak; Dariusz Kusiak; Branko Koprivica; Marko Rosić; Srđan Divac (Applied Sciences, 2023)
A description of magnetic hysteresis is important for the prediction of losses in soft magnetic materials. In this paper, a viscosity-type equation is used to describe dynamic hysteresis loops in an amorphous ring core for symmetric excitation, as prescribed by international standards. The value of the exponent appearing in the viscosity-based equation can be assumed to be constant if the maximum induction is away from the saturation value. The viscosity-type equation is used to describe the shape variation of magnetization curves due to eddy currents in different time and space scales. Modeling is carried out for various excitation frequencies and induction amplitudes. The discrepancies between the experimental and modeled curves (and also losses) are acceptable in the wide range of the frequency and maximum induction. The paper indicates that the viscosity-type effects, mostly due to eddy currents generated in the conductive material, play an important role in energy dissipation at increased excitation frequencies. The modeling results might be interesting to the designers of magnetic circuits.